Preoperative Cervical Cobb Angle Is a Risk Factor for Postoperative Axial Neck Pain after Anterior Cervical Discectomy and Fusion with Zero‐Profile Interbody. Issue 12 (17th October 2022) - Cao, Yuan; Xu, Chen; Sun, Baifeng; Cui, Chen; Zhang, Ke; Wu, Huiqiao; Qi, Min; Xi, Yongming; Yuan, Wen; Shen, Xiaolong; Liu, Yang
Abstract : Objectives: Anterior cervical discectomy and fusion (ACDF) with zero‐profile interbody has a lower incidence of complications in treating cervical spondylotic myelopathy (CSM). However, postoperative axial neck pain is still commonly occurred, and the factors affecting which is not known. Here, we retrospectively analyze the risk factors for postoperative axial pain after performing ACDF with zero‐profile implant in single‐level CSM. Methods: Patients who suffered from single‐level CSM and who received ACDF with zero‐profile implant between 2018 January to 2020 December were reviewed. Of 180 single‐level CSM patients, 144 patients who passed the inclusion criteria were enrolled. Patients were divided into two groups according to the severity of postoperative axial pain as measured by postoperative neck visual analogue scale (nVAS). Clinical parameters including age, sex, smoking history, symptom duration, body mass index (BMI), the Japanese Orthopaedic Association (JOA) scores, as well as radiological parameters were obtained pre‐ and post‐operatively, and the data were compared between two groups. Pearson's chi‐square tests and Mann–Whitney U tests were implemented to identify statistically significant differences between subgroups for categorical and continuous data, respectively; otherwise, the data were tested with Student's t ‐test. Risk factors were identified using logistic regression. Results: Of the patients (97.8%) achieved satisfied neurological recovery, and 88.2% of the patients achieved fusion at 1‐year follow‐up. 33% of the patients (48 patients out of 144) had sustained postoperative axial pain after the surgery. Comparison of different severity groups exhibited no significant differences in terms of the possible risk factors ( P > 0.05) except for pre‐ and post‐operative C2–C7 Cobb angles (6.33 ± 6.53 vs. 11.88 ± 7.41, P < 0.05; 13.49 ± 5.31 vs 16.64 ± 7.34, P < 0.05). Furthermore, correlation analysis showed that the preoperative C2–C7 Cobb angle is significantly correlated with the severity of the postoperative axial pain (R 2 = 0.83, P < 0.01). In addition, logistic regression analysis demonstrated that the preoperative C2–C7 Cobb angle is an independent predictor of postoperative axial pain ( P < 0.01, OR = 0.53). Further receiver operating characteristic (ROC) analysis displayed an area under the curve (AUC) of 0.78 ( P < 0.01) for preoperative C2–C7 Cobb angle, and the optimal cutoff was 8.4° (sensitivity 0.77, specificity 0.65). Conclusion: The pre‐operative C2–C7 Cobb angle is a risk factor for severe postoperative axial pain after anterior cervical discectomy and fusion with zero‐profile interbody, and we should be cautious when poor preoperative C2–C7 Cobb angle is found in myelopathy patients planning to use zero‐profile interbody to treat such patients. Abstract : We focused on deciphering the risk factors of postoperative axial pain after anterior cervical discectomy and fusion (ACDF) with zero‐profile implant in single‐level CSM in this study. Through comparison of the clinical and radiological parameters of severe and mild axial pain patient groups, we found that pre‐operative C2–C7 Cobb angle significantly affects the incidence of severe postoperative axial pain. Our data showed that indications for zero‐profile implant should be carefully determined in myelopathy patients with poor pre‐operative C2–C7 Cobb angle.